Krasnosel’skii Type Hybrid Fixed Point Theorems and Their Applications to Fractional Integral Equations - H. M. Srivastava; Sachin V. Bedre; S. M. Khairnar; B. S. Desale (Abstract and Applied Analysis)
Some hybrid fixed point theorems of Krasnosel’skii type, which involve product of two operators, are proved in partially ordered normed linear spaces. These hybrid fixed point theorems are then applied to fractional integral equations for proving the existence of solutions under certain monotonicity conditions blending with the existence of the upper or lower solution.